The Missões ART project in the sertão cearense: oral health care beyond the dental office (Research, Society and Development, 2022)
With the aim of facilitating the access of the most needy communities, especially school-age children, to quality preventive and curative dental care, the Missões ART project was created. Objective: to describe the activities of the Missões ART project of the Dentistry course at the Federal University of Ceará and to expose the impact of these actions on the population. Method: This is a report about the experience in field actions of the Missões ART project in the years 2018 and 2019 in the northern region of the state of Ceará. Results: Oral health care actions were carried out with children of public school. The actions were carried out in a school environment and included oral health education activities with a problematizing nature, supervised brushing and the performance of Atraumatic Restorative Treatment, in addition to other dental procedures that could be performed outside conventional clinical environment. Final considerations: The experience gathered from the Missões ART project makes the importance of university extension even more evident, in the sense of qualifying teaching based on the needs of the community.